Pottery, pavements, and paradise : iconographic and textual studies on late antiquity - Hoek, Annewies van den. (Vigiliae Christianae, Supplements, 2013)
These essays on late antiquity traverse a territory in which Christian and pagan imagery and practices compete, coexist, and intermingle. The iconography of the most significant late antique ceramic, African Red Slip Ware, is an important and relatively unexploited vehicle for documenting the diversity and interpenetration of late antique cultures. Literary texts and art in other media, particularly mosaics, provide imagery that complement and enhance the messages of the ceramics. Popular entertainments, pagan cults, mythic heroes, beasts, monsters, and biblical visions are themes dealt with on the patrician and popular levels. With interpretive supplements from these diverse realms, it is possible to achieve greater insight into the life, attitudes, and thought of Late Antiquity.